2019
DOI: 10.3390/en12122373
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Assessment of a Novel Drywall System Insulated with VIPs

Abstract: Advanced building envelopes targeting high energy performance should combine high thermal performance with easy and fast installation. The combination of lightweight steel-framed building systems with vacuum insulation panels (VIPs) form an attractive solution toward this requirement. In the present study, a lightweight metal frame drywall building insulated with VIPs is constructed and experimentally/theoretically investigated, focusing on the impact of every type of thermal bridges on the thermal performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In general, the blends developed in this study presented an average density of 950 kg/m 3 with a mean thermal conductivity of 0.22 W/m K. When compared to some materials traditionally used by construction industries such as the gypsum and cement boards, a thermal conductivity of 0.27 and 0.35 W/m K, respectively, was presented but with a higher density than PP/LGNa blends, ranging from 1033 to 1150 kg/cm 3 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the blends developed in this study presented an average density of 950 kg/m 3 with a mean thermal conductivity of 0.22 W/m K. When compared to some materials traditionally used by construction industries such as the gypsum and cement boards, a thermal conductivity of 0.27 and 0.35 W/m K, respectively, was presented but with a higher density than PP/LGNa blends, ranging from 1033 to 1150 kg/cm 3 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The installation of the sensor outside the cold storage is installed behind the cold storage trucks to prevent wind and pressure coming into contact with the sensor, resulting in inaccurate measurements. The Temperature measurement location, as shown in Figure 5 [15] and how to install an additional VIPs in a cold room, as shown in Figure 6 [16].…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, research studies focusing on the indoor thermal environment of the LSF construction system can be found, including the monitoring of test cells with significant dimensions and current construction solutions [24][25][26]; however, these studies overlook construction features representative of real structures, such as windows, limiting the correlation with real scenarios. Moreover, some experimental comparative studies between high and low thermal inertia construction methods can also be found in the literature; however, the climates involved are very different from Southern European, with a prevalence of hot-arid desert [27,28], hot-summer [29], oceanic temperate [30], and subtropical humid [31] climates.…”
Section: Introductionmentioning
confidence: 99%